Schiff's Diseases of the Liver 2011
DOI: 10.1002/9781119950509.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Tests

Abstract: Key conceptsr Biochemical tests can be used to detect acute injury to the liver and chronic diseases of the liver before development of symptoms.r Elevations in serum levels of aminotransferases (aspartate aminotransferase and alanine aminotransferase) reflect hepatocellular injury and/or permeability of the liver cell membrane, but do not correlate with the extent of fibrosis or measures of metabolic functions of the liver.r An elevation of serum alkaline phosphatase occurs in response to intrahepatic cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 103 publications
(114 reference statements)
1
1
0
Order By: Relevance
“…In another study, they reported also that increment of ALT and AST reflects hepatocyte damages and the increment of ALP refers to cholestasis, 61 which is in complete agreement with the current obtained results. The elevated levels of ALT, AST, and ALP in the current study in DG-treated group indicated the incidence of severe hepatic damages and cellular injuries.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, they reported also that increment of ALT and AST reflects hepatocyte damages and the increment of ALP refers to cholestasis, 61 which is in complete agreement with the current obtained results. The elevated levels of ALT, AST, and ALP in the current study in DG-treated group indicated the incidence of severe hepatic damages and cellular injuries.…”
Section: Discussionsupporting
confidence: 90%
“…Decrease in albumin may be due to decrease protein synthesis which results from deficits in regulations or trauma to the hepatocytes, as in the severity of liver disease, serum albumin reduces indicting diminished albumin synthesis (Limdi and Hyde, 2003). Data from this study showed that albumin was slightly decreased in the treated groups compared to control, but decreases in serum albumin is not specific for liver disease and though their decreased levels may be associated with protein malnutrition, and nephrotic syndrome (Daniel and Marshall, 1999). However, serum albumin levels may be normal in diseases like drug related hepatotoxicity, acute viral hepatitis and obstructive jaundice (Thapa and Walia, 2007).…”
Section: Discussionmentioning
confidence: 62%
“…They are made up of ALT and AST. 8 The test offering the best ease and sensitivity remains to be the traditional marker GGT. Combining it with other conventional markers like aminotransferases (AST, ALT) and certain measures that show the severity and prognosis, including total proteins, albumin, bilirubin, and PT, can improve its diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%